Listening Skill At Tertiary Level: A Reflection - Abedin, Md Minhajul; Majlish, Saiful Hassan Khan; Akter, Shorna (Dhaka University Journal of Linguistics, 2010)
This study focuses on the real scenario of listening skill of learners at the tertiary level in private universities in our country and through this attempt we have tried to find out the reasons of poor listening skills of the learners. At secondary and higher secondary level, where Communicative Language Teaching (CLT) is in practice, writing and speaking are given maximum importance. Since learners' listening skill is not assessed like other skills, it remains unattended through out their academic career. The scenario of poor listening skill of the learners continues with the same negligence even at the tertiary level. Giving importance to the development of this skill, the study has been done throughout questionnaire survey both from students' and teachers' point of view. The survey result has been analyzed and some suggestions are given regarding the matter. Key words: Listening Skill, Tertiary level, Private Universities DOI: 10.3329/dujl.v2i3.4144 The Dhaka University Journal of Linguistics: Vol.2 No.3 February, 2009 Page: 69-90